Generalization of the Central Subgroup of the Nonabelian Tensor Square of a Crystallographic Group with Symmetric Point Group - Masri, Rohaidah; Ting, Tan Yee; Idrus, Nor’ashiqin Mohd. (Journal of Informatics and Mathematical Sciences, 2016)
The central subgroup of the nonabelian tensor square of a group denoted by is a crucial tool in exploring the properties of a group. It is a normal subgroup generated by the element for all In this paper, the central subgroup of the nonabelian tensor square of a crystallographic group with symmetric point group is constructed and generalized up to finite dimension.